2018
DOI: 10.1029/2018tc005043
|View full text |Cite
|
Sign up to set email alerts
|

Kinematics of Late Quaternary Slip Along the Qishan‐Mazhao Fault: Implications for Tectonic Deformation on the Southwestern Ordos, China

Abstract: The northwest striking Qishan‐Mazhao fault (QMF) accommodates complex deformation in the Tibet‐Ordos transition zone. We studied the geologic and geomorphic expression of the QMF using interpretations of high‐resolution satellite images and structure‐from‐motion models combined with detailed field investigations. Displaced loess tablelands, stream channels, and fluvial terraces show that the QMF is predominately a left‐lateral strike‐slip fault with a minor normal component. The magnetic susceptibility and opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 30 publications
(50 reference statements)
3
25
1
Order By: Relevance
“…Thermochronological data from the northeastern Tibetan Plateau and the evidence from the foreland basin are consistent with the northward propagation of thrusts Figure 1. Information on the growth and rotation of the northeastern Tibetan Plateau (orange arrows) is from Tapponnier et al [2], Dupont-Nivet et al [19], Yu et al [72], Li et al [73], and Zhang et al [74]. Data are derived from the following: (1) Fang et al [16]; (2) Wang et al [12]; (3) Lease et al [41]; (4) Fang et al [11]; (5) Wang et al [75]; (6) Clark et al [14]; (7) Duvall et al [15]; (8) Liu et al [60]; (9) Mock et al [63]; (10) Roger et al [62]; (11) Wang et al (2012); (12) Tian et al [46]; (13) Yang et al [25]; (14) Duvall et al [76]; (15) Yu et al [77]; (16) Lease et al [56]; (17) Zheng et al [65]; (18) Wang et al (2012); (19) Liu et al [24]; (20) Yu et al [69]; (21) Zhang and Xue [36]; (22) Tian et al [52]; (23) Tian et al [78]; and (24) Clark et al [13].…”
Section: Implications For Deformation Of the Ne Tibetan Plateaumentioning
confidence: 99%
“…Thermochronological data from the northeastern Tibetan Plateau and the evidence from the foreland basin are consistent with the northward propagation of thrusts Figure 1. Information on the growth and rotation of the northeastern Tibetan Plateau (orange arrows) is from Tapponnier et al [2], Dupont-Nivet et al [19], Yu et al [72], Li et al [73], and Zhang et al [74]. Data are derived from the following: (1) Fang et al [16]; (2) Wang et al [12]; (3) Lease et al [41]; (4) Fang et al [11]; (5) Wang et al [75]; (6) Clark et al [14]; (7) Duvall et al [15]; (8) Liu et al [60]; (9) Mock et al [63]; (10) Roger et al [62]; (11) Wang et al (2012); (12) Tian et al [46]; (13) Yang et al [25]; (14) Duvall et al [76]; (15) Yu et al [77]; (16) Lease et al [56]; (17) Zheng et al [65]; (18) Wang et al (2012); (19) Liu et al [24]; (20) Yu et al [69]; (21) Zhang and Xue [36]; (22) Tian et al [52]; (23) Tian et al [78]; and (24) Clark et al [13].…”
Section: Implications For Deformation Of the Ne Tibetan Plateaumentioning
confidence: 99%
“…Using geological data and earthquake focal mechanism solutions, Li. et al [17] concluded that the late Quaternary activity of the QSMZF is left-lateral with normal component, with a strike-slip rate of about 0.5-1.0 mm/yr. In the LXB, the negative dilatation was the first-order feature, while a positive dilatation belt with a north-northeast direction was mapped in the central part of LXB.…”
Section: Gps-derived Strain Ratesmentioning
confidence: 99%
“…The Qian River drainage of which the tectonic framework is controlled by the Longxian-Baoji active fault zone (F5 in Figure 1a) is located in the neo-tectonic movement active area (Li et al, 2018b;Shi, 2011;Zheng et al, 2016). It also located in the middle-north segment of the famous south-north earthquake belt, and some moderate-large earthquakes are known to have occurred, such as the Qishan 7.0 magnitude earthquake in 780a BC and the Longxian 6.0 magnitude earthquake in 1704 a (Shi, 2011;Wang, 2011a;Zheng et al, 2016).…”
Section: Geological Andgeographical Settingmentioning
confidence: 99%